Morning administration enhances humoral response to SARS-CoV-2 vaccination in kidney transplant recipients - Zahradka, Ivan; Tichanek, Filip; Magicova, Maria; Modos, Istvan; Viklicky, Ondrej; Petr, Vojtech (American journal of transplantation, 2024)
Although severe acute respiratory syndrome coronavirus 2 messenger ribonucleic acid (SARS-CoV-2 mRNA) vaccines are effective in kidney transplant recipients (KTRs), their immune response to vaccination is blunted by immunosuppression. Other tools enhancing vaccination response are therefore needed. Interestingly, aligning vaccine administration with circadian rhythms (chronovaccination) has been shown to boost immune response. However, its applicability in KTRs, whose circadian rhythms are likely disrupted by immunosuppressants, remains unclear. To assess the impact of vaccination timing on seroconversion in the KTRs population, we analyzed data from 553 virus-naïve KTRs who received 2 doses of messenger ribonucleic acid (mRNA) vaccine. Bayesian logistic regression was employed, adjusting for previously identified predictors of seroconversion, including allograft function, maintenance immunosuppressants, or time since transplantation. SARS-CoV-2 immunoglobulin G (IgG) levels were measured with a median of 47 days after the second dose. The results did not reveal a reliable effect of timing of the first dose but did indicate that earlier timing for the second dose brings a notable benefit-every 1-hour delay in the application was associated with a 16% reduction in the odds of seroconversion (OR 0.84, 95% CI 0.71, 0.998). Similar results were obtained from quantile regression modeling IgG levels. In conclusion, morning vaccination is emerging as a promising and easily implementable strategy to enhance vaccine response in KTRs.
Keywords: dospělí; COVID-19; immunosuppression; protilátky virové; Immunoglobulin G; humorální imunita; vaccination timing; Kidney Transplantation; imunosupresiva; Humans; lidé středního věku; seroconversion; Middle Aged; Transplant Recipients; Antibodies, Viral; transplantace ledvin; cirkadiánní rytmus; chronovaccination; mužské pohlaví; Immunity, Humoral; Kidney Failure, Chronic; Adult; vaccination response; COVID-19 Vaccines; SARS-CoV-2 mRNA vaccines; příjemce transplantátu; imunoglobulin G; Bayesian modeling; ženské pohlaví; rejekce štěpu; vakcíny proti COVID-19; Immunosuppressive Agents; lidé; SARS-CoV-2; chronické selhání ledvin; Vaccination; Graft Rejection; Aged; circadian rhythms; senioři; Male; kidney transplantation; vakcinace; Circadian Rhythm; Female